Dampak Covid-19 Terhadap UMKM Konveksi di Kecamatan Mojowarno Kabupaten Jombang - Michael Firdaus; Lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2022)
During the current Covid-19 pandemic, many changes have occurred, such as people's incomes which are decreasing due to the current pandemic. And one of the sectors experiencing the impact of Covid-19 is the economy. Because it is well known that humans can not be separated from the name of the economy. Humans can survive, humans can fulfill all their needs such as clothing, food and shelter because of the economy. This research took place in Wringinpitu Village, Mojowarno District, Jombang Regency. With this research, the aim is to find out how influential the impact of the Covid-19 pandemic is on the income of convection MSME actors in the past and the current covid pandemic which is located in the Mojowarno sub-district, Jombang district. The research method used is descriptive qualitative method, using primary data sources from information obtained through direct sources and secondary reference journals related to this research. Keywords : Covid-19, Cooperative SMEs, Wringinpitu, Economy